Design and fabrication of vegetables dicer / Muhammad Luqman Nasaruddin And Zeno Michael - Nasaruddin, Muhammad Luqman; Michael, Zeno (School of Mechanical Engineering, 2023)
This project aims to address the challenges posed by time-consuming and potentially contaminating manual vegetable slicing tasks by proposing the development of an automated vegetable cutting system. By leveraging advanced technology and equipment, the system aims to minimize the need for human effort and time while ensuring precise and efficient vegetable cutting. The primary focus is on maintaining high standards of hygiene and safety, reducing the risks of contamination and foodborne illnesses. The project involves comprehensive research and development to identify the most suitable technology, machinery, and equipment for the automated cutting process. Through thorough testing and optimization, the final product is designed and fabricated to deliver efficiency, effectiveness, and safety, specifically tailored to the requirements of hostels and restaurants. The introduction of this automated vegetable cutting system promises to significantly enhance the quality and efficiency of food preparation in the hospitality industry, streamlining operations, reducing human effort, and ensuring strict adherence to hygiene and safety standards